Analysis of Self-Regulated Learning of Students in Mathematics Education Study Program in Number Theory Course - Dirgantoro, Kurnia Putri Sepdikasari; Soesanto, Robert Harry (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2021)
The number theory is the first mathematics content course in the UPH FIP Mathematics Education study program, which does not have a response class. The response class was conducted as a companion to four content subjects with close relations with school mathematics content, namely Calculus 1, Calculus 2, Geometry, and Linear Algebra. Based on the questionnaire that has been distributed, prospective mathematics teachers consider that the response class is beneficial for them in attending lectures and in exploring related mathematical concepts. However, on the other hand, students inevitably have to go back to learning to be determined with the response class. The implication is that students' self-regulated learning will not develop optimally. However, self-regulated learning is an essential aspect that prospective teachers need to have. This research was conducted to see how self-regulated learning of future mathematics teachers in number theory courses. The research instruments used are questionnaires, the scale of self-regulated learning, and interviews. This research is a qualitative descriptive study. The results of this study are that most students have a moderate level of learning independence. The aspects or indicators of learning independence that need special attention are setting learning goals/targets. Prospective teacher students need to continue to train and develop their learning independence to become professional teachers who continue to develop along with the times.